2010
DOI: 10.1007/s11633-010-0509-5
|View full text |Cite
|
Sign up to set email alerts
|

Sliding mode variable structure control for visual servoing system

Abstract: A visual servoing tracking controller is proposed based on the sliding mode control theory in order to achieve strong robustness against parameter variations and external disturbances. A sliding plane with time delay compensation is presented by the pre-estimate of states. To reduce the chattering of the sliding mode controller, a modified exponential reaching law and hyperbolic tangent function are applied to the design of visual controller and robot joint controller. Simulation results show that the visual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…In fact, the transpose of the Jacobian matrix has already been used in robotics for continuous control laws due to its simplicity() among others. However, to the best of the authors' knowledge, it has not been yet used for SMC, eg, all the SMCs proposed in literature for robot VS() use the Jacobian pseudoinverse.…”
Section: Smc Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the transpose of the Jacobian matrix has already been used in robotics for continuous control laws due to its simplicity() among others. However, to the best of the authors' knowledge, it has not been yet used for SMC, eg, all the SMCs proposed in literature for robot VS() use the Jacobian pseudoinverse.…”
Section: Smc Theorymentioning
confidence: 99%
“…It is interesting to note that the sliding surface given by Equation has already been used in VS for an SM velocity controller in previous works. ()…”
Section: Smc For Reference Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation results showed that the control scheme can achieve good tracking performance and has strong robustness against parameter variations and external disturbances. Hence, we will focus here on a variable structure control with sliding mode, which proved its potential in visual servoing system [29].…”
Section: Visual Servoing Based On the Fuzzy Adaptive Kalman Filtermentioning
confidence: 99%
“…Since the early work of Shirai and Inoue [1] (who described how a visual feedback loop can be used to correct the position of a robot to increase task accuracy), considerable efforts have been devoted to the visual control of robot manipulators [2] . Traditional robot visual servo control system is based on calibration technique that needs to know the intrinsic parameters of the camera, the hand-eye transformation, and the parameters of robot kinematics, so that the control precision of the servo system depends largely on the precision of calibration [3] .…”
Section: Introductionmentioning
confidence: 99%